Evaluation Study of the Joint Movement Strategy “Geber” in Improving the Preservation of Pananjung Pangandaran - Rizky, Fahmi Muhamad; Maryani, Enok (Journal of Event, Travel and Tour Management, 2024)
Cagar Alam Pananjung, located in West Java, is a nature reserve rich in biodiversity and a popular tourist destination. This study evaluates the Joint Movement Strategy (Geber) in conserving this nature reserve through collaboration between the government and the community. A qualitative research method with a descriptive analytical approach was used, relying on literature review from various relevant sources. The study results indicate that the implementation of the Geber strategy faces various challenges and opportunities. The role of the government in coordinating and implementing environmental policies and managing the nature reserve is crucial. However, there is a need to strengthen monitoring mechanisms and law enforcement. Active participation of the local community is also significant in managing the nature reserve through education, training, and empowerment. The study's recommendations include improving coordination between government agencies and monitoring mechanisms, as well as increasing community participation through education and training. The government is also advised to facilitate partnerships with the private sector and non-governmental organisations to support conservation efforts. In conclusion, collaboration between the government and the community is essential to enhance the conservation of Pananjung Pangandaran nature reserve. Effective implementation of the Geber strategy is expected to preserve this nature reserve for the well-being of future generations.